Replacing Medicaid with an Imperfect Substitute: Implications for Health Inequality - Randall Q. Akee; Timothy J. Halliday; Teresa Molina (RSF: The Russell Sage Foundation Journal of the Social Sciences, 2023)
A 2015 policy change substantially increased the administrative burden involved in accessing health insurance for Pacific Islander immigrants in Hawaii. We examine the heterogeneous health-care use effects of this policy, which revoked Medicaid eligibility for these migrants and replaced it with access to subsidized private health insurance. Using data on the universe of hospitalizations and emergency room visits in Hawaii, we classify individuals as high or low risk based on their use in a baseline period. We then use a difference-in-differences strategy to estimate the effects of the policy on use, separately for low-risk and high-risk groups. The policy exacerbated health inequality: high-risk individuals experienced larger reductions in total use and larger increases in uninsured use.